1997
DOI: 10.1159/000174161
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic Blood Pressure Dysregulation and Cytosolic Calcium in Primary Hyperparathyroidism

Abstract: The purpose of this study was to characterize the changes in noradrenergic blood pressure regulation and the causes of this dysregulation in patients with histologically proven primary hyperparathyroidism before and after parathyroidectomy. In untreated hypertensive patients with primary hyperparathyroidism slightly higher plasma levels of norepinephrine, enhanced cardiovascular reactivity to norepinephrine (p < 0.05) and increased cytosolic free calcium concentration in platelets (p < 0.05) were found. Parath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
2
7
0
1
Order By: Relevance
“…According to some authors, this prevalence may vary from 20 to 80%. [2][3][4][5] The results of our study confirm and extend these data reported in the 30,31 (c) renal function injury; 7,8 (d) activation of the renin-angiotension-aldosterone system; [32][33][34] (e) activation of the sympathetic nervous system; 26,29 (f) activation of the endothelin 35 and adrenomedullin 36 systems.…”
Section: Discussionsupporting
confidence: 83%
“…According to some authors, this prevalence may vary from 20 to 80%. [2][3][4][5] The results of our study confirm and extend these data reported in the 30,31 (c) renal function injury; 7,8 (d) activation of the renin-angiotension-aldosterone system; [32][33][34] (e) activation of the sympathetic nervous system; 26,29 (f) activation of the endothelin 35 and adrenomedullin 36 systems.…”
Section: Discussionsupporting
confidence: 83%
“…The close correlation between PTH and intracellular calcium suggests that PTH may act as an ionophore for calcium entry into cells and perhaps reflect a pre-hypertensive condition in normotensive patients with pHPT. Increased cytosolic free calcium in platelets has been shown to be elevated also in untreated hypertensive patients with pHPT (Schiffl et al 1997). Moreover, parathyroidectomy of these patients resulted in the reduction of cytosolic free calcium and led to normotension.…”
Section: Effect Of Primary Hyperparathyroidism On Blood Pressurementioning
confidence: 99%
“…In some studies, it has been observed that PTH decreases intracellular calcium [28, 39, 40, 41, 42], and it was even observed that this hormone acts in the vascular smooth muscle by blocking the entrance of this ion through voltage-dependent L-type calcium channels [39, 40, 41, 42]. There are also studies in which PTH did not alter intracellular calcium [43]. PTH may also display calciotropic properties in cardiac cells [44], osteoblast-like cells [45], renal proximal tubular cells [46], and hepatic cells [47]and could even cause a transient increase in intracellular calcium in cultured vascular smooth muscle cells opening calcium channels [48].…”
Section: Introductionmentioning
confidence: 99%